A variação de tempo-modo e conexão nas orações condicionais em português - Gryner, Helena (1990)
Investigates the variation in tense-mood forms of hypothetical conditional clauses of Portuguese spoken in Rio de Janeiro and in the way these clauses are connected in actual discourse. Four variables are examined: future subjunctive, present indicative, gerund and juxtaposition. It starts with the description of the phenomenon at issue and lhe presentation of the theoretical foundation of the research, basically the principles of the theory of linguistic variation. Sampling procedures are then defined, followed by a description of methodological aspects concerning the gathering and treatment of the data. Next, a review of the literature on conditionals and verbal modality is presented, as treated by logic, traditional grammar and contemporary linguistics. In the main part of the dissertation, there is a description of the sets of factors which proved relevant for determining the variables above mentioned . Social factors and linguistic ones, syntactic, semantic, pragmatic - discoursive contexts related to the emergence of the variables are specified, and their mutual complementarities are established. As for social factors, it is shown that level of education is relevant to informants who have to function within institutions that value formal language. It is argued that a quantitative analysis of the contexts must be carried out for determining the variables that carry meaning. Thus, this dissertation proposes the need for a comprehensive framework which may provide explanation that will enlarge both the theoretical field and the knowledge of social practice of language, as it integrates the systematic and the discoursive, the linguistic and the social aspects of language.